Single- and Double-Entry Volume Equations for Turkey Oak (Quercus cerris L.) Stands in Bursa Regional Directorate of Forestry - Sönmez, Turan; Gencal, Burhan; Cankaya, Ergin Cagatay (My University, 2023)
Tree volume estimates are the essential databank used in estimates of forest growth and revenue. In various workshops, symposiums, and general assemblies, it is emphasized that oaks with 18 species in Turkey should be handled on a species basis. For this purpose, in our study, equations were determined for the volume estimates of the Turkey oak (Quercus cerris L.) stands, which were distributed within the scope of the Bursa Regional Directorate of Forestry. Sample areas of all ages and site classes were selected through the data obtained from the management plans, and the required sampling distribution was made. Five single-entry tree volume equations and 40 double-entry tree volume equations proposed by different sources were tried. The most appropriate volume equations were determined according to their relative rankings created using seven different eligibility criteria (coefficient of determination, mean squared error, mean absolute percentage error, root mean square error, average absolute error, Akaike information criterion, and Schwarz’s Bayesian information criterion). As a result of the ranking, equation 5 was selected for single-entry tree volume equations and equation 34 was selected for double-entry tree volume equations. The results are R2 = .9586 for 34th equation and R2 = .9016 for 5th equation, respectively. The equations were compared with the test data, and it was seen that they could be used by the Regional Forest Directorate of Bursa. At the same time, it was compared with the ready-made double-entry volume tables developed and published earlier. As a result, it was determined that there were statistical differences in the volume tables.
Keywords: Biyoloji; Ziraat Mühendisliği